EDUCATIONAL-SCIENTIFIC SYSTEM OF FORMATION OF SCIENTIFIC AND PEDAGOGICAL HIGHER QUALIFICATION STAFF IN DIGITAL TRANSFORMATION OF UKRAINIAN EDUCATION AND SCIENCE (to mark the 20th anniversary of the Institute of Information Technologies and Learning Tools) - Bykov В.Ю.; Iatsyshyn А.В. (Journal of Information Technologies in Education (ITE), 2019)
Training of highly qualified specialists is recognized as one of the most authoritative branches of the national educational system. At the Institute of Information Technologies and Learning Tools of the National Academy of Educational Sciences of Ukraine considerable attention is paid to the training of scientific and scientific-pedagogical staff of higher qualification, i.e., the center of training and certification of a new generation of scientific and scientific-pedagogical staff to ensure the process of education and science digitalization in Ukraine is postgraduate, doctoral and specialized scientific council. The article covers the experience of the Institute of Information Technologies and Learning Tools of the of the National Academy of Educational Sciences of Ukraine in the context of training and certification of scientific and scientific-pedagogical staff of higher qualification. The initiative to create a scientific specialty 13.00.10 - information and communication technologies in education, which is aimed at solving the problem of training postgraduate and doctoral students conducting research to ensure the process of digitalization of education, is described. The role of the Institute of Information Technologies and Learning Tools of the National Academy of Educational Sciences of Ukraine in the issues of digitalization of education and science of Ukraine is emphasized. The Concept of development of digital economy and society of Ukraine for 2018-2020 is analyzed and it is determined that it does not mention at all the importance of training the personnel for digital transformation of economy and society, in particular of those who will carry out these processes, also does not point out the importance of conducting previous scientific research to make these processes effective and efficient. Organizational and pedagogical conditions for providing effective training of scientific and scientific and pedagogical staff of higher qualification and experience of their implementation at the Institute of Information Technologies and Learning Tools of the National Academy of Educational Sciences of Ukraine are presented and analyzed. The educational and scientific system of formation of scientific and scientific-pedagogical staff of higher qualification on digital transformation of Ukrainian education and science and interaction of the Institute of Information Technologies and Learning Tools of the National Academy of Educational Sciences of Ukraine and other institutions in its implementation have been developed and substantiated.